Identification and Characterisation of Amylolytic Bacteria from Tuber and Cereal Processing Units and Dumpsites in Kumasi - Mintah, Francis Dadzie (KNUST, 2026)
A Thesis Submitted To The Department of Biochemistry and Biotechnology, Kwame Nkrumah University of Science and Technology, in Partial Fulfilment of The Requirement for the Award of Master of Philosophy in Biotechnology